KONSEP QATHâI DAN ZHANNI AL-DALALAH DAN PENGARUHNYA TERHADAP PENAFSIRAN AL-QURâAN - Firdaus, Firdaus (Jurusan Syariah dan Ekonomi Islam STAIN Parepare, 2013)
This article describes the problem and the concept qathi zhanni al-dalalah and its influence on the interpretation of the Quran. From the results obtained literatus assessment some understanding that the Quran as the word of Allah, there is no difference of opinion among Muslims regarding the truth of the source, ie from Allah. Muslims also have the same belief that the editorial verses of the Quran were collected in the manuscripts is the same without the slightest difference to that received by the Prophet Muhammad. Of Allah. through the Angel Gabriel. Layout differences among Muslims is in terms of editorial content of the meaning of the verses of the Quran. Usul Fiqh Scholars divide the texts of the Quran to the two components, namely qathi and zhanni al-dalalah. Qathi al-dalalah is clear and certain passages that have only one meaning, and not open to other meanings. While al-dalalah zhanni is the opposite of qathi al-dalalah, he was open to interpretation. Another interpretation by scholars, he did not make the classification of passages of the Quran, that there is no one zhanni qathi and al-dalalah, because he thinks in that way it was meant to limit the meaning, and interpretation al-Qur an. In the Quran it is able to contain a lot of interpretation. With the concept of al-dalalah qathi by scholars Usul Fiqh course is unfavorable interpretations among scholars, because the concept was meant to limit the meaning efforts, interpretation of the texts of the Quran itself. But the concept of al-dalalah zhanni by Ulama Usul Fiqh, wide open opportunities to interpret, interpret the texts of the Quran was, in a sense have a major impact and positive influence on the birth of the commentators and the mujtahid.